Ethical decision making in school mental health - Raines, James Curtis; Dibble, Nic T. (New York ; Oxford : Oxford University Press, 2011)
Beginning with an introduction to the moral, legal, and clinical foundations that undergird ethical practice, the authors outline an ethical decision-making process to handle conundrums that includes 7 major steps: know yourself, analyse the dilemma, seek consultation, identify courses of action, manage the clinical concerns, enact the decision, and reflect on the process.
Description based on print version record.
Includes bibliographical references and index.
Keywords: School children -- Mental health services -- United States; School children -- Mental health services -- Moral and ethical aspects; School psychology -- United States; School social work -- United States; School health services -- United States